ANALISIS TITIK IMPAS DAN BATAS AMAN SEBAGAI DASAR PERENCANAAN LABA JANGKA PENDEK PADA PT. SOHO INDUSTRI PHARMASI CABANG MANADO - Tangeren, Rachel; Sondakh, Jullie J.; Pontoh, Winston (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
The main purpose of a company is to make a profit. Profits are not obtained automatically but it has to require a good planning. Tools that can be used by company management in planning earnings are breakeven analysis and margin of safety. Break even analysis studies company return point and margin of safety provides the information of the company sales before suffering a loss. The purpose of this study is to determine the breakeven point and margin of safety of PT. SOHO Industri Pharmasi Cabang Manado in the specific periodes so it can be used as a tool to plan for the future earnings. The analytical method used is qualitative with descriptive approach. The results of the study shows that in 2016-2017 the company is able to sells its product above the breakeven point which means they earned profits and the percentage of margin of safety is large which means the company is far from the point of loss.Keywords: Breakeven Point, Margin of Safety, Profit Planning